2008
DOI: 10.1369/jhc.2008.952234
|View full text |Cite
|
Sign up to set email alerts
|

Expression of H+,K+-ATPase and Glycopattern Analysis in the Gastric Glands of Rana esculenta

Abstract: A multidisciplinary study involving lectin histochemistry, IHC, immuno-lectin blotting, and immunogold was carried out to determine the distribution of sugar residues in the glycoproteins of Rana esculenta oxynticopeptic cells. We considered animals in two experimental conditions, fasting and fed. It is known that, in mammals, the tubulovesicular membranes are rich in proteins with several functions. The proton pump H+,K+-ATPase, a heterodimeric complex with a catalytic α-subunit and a heavily glycosylated β-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In anurans, mucins are produced by goblet cells found in the esophagus and the intestines, but also by epithelial cells and mucous neck cells in the stomach [43]. In R. icterica, mucous neck cells of fundic region produce neutral glycoprotein, rich in galactose residues, similar to those of R. esculenta [19], Ceratophrys ornata [44], Ceratophrys chalcides [10], and reptile Natrix natrix [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In anurans, mucins are produced by goblet cells found in the esophagus and the intestines, but also by epithelial cells and mucous neck cells in the stomach [43]. In R. icterica, mucous neck cells of fundic region produce neutral glycoprotein, rich in galactose residues, similar to those of R. esculenta [19], Ceratophrys ornata [44], Ceratophrys chalcides [10], and reptile Natrix natrix [45].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, our results corroborated the reports by Loo and Wong [3], who described that the lining epithelial cells of the stomach of B. viridis and B. melanostictus produce only neutral mucins. Moreover, lectin histochemical studies revealed that in R. aurora aurora [13], B. viridis [14], and R. esculenta [19] mucous secreting superficial cells produce galactose, but not galactosamine, since in B. viridis [14] and R. aurora aurora [13] gastric secretion is rich in galactose and mannose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pellets of empty liposomes or 10His-OsPIP1; 1 proteoliposomes obtained by centrifugation at 152,000 g for 1 h at 4 C were fixed in a mixture of 3% paraformaldehyde and 1% glutaraldehyde in 0.1 mol/l PBS at pH 7.4 for 4 h at 4 C. Specimens were postfixed in 1% OsO 4 in PBS for 1 h at 4 C. Fixed specimens were dehydrated in ethanol and then embedded in Epoxy Resin-Araldite (M) CY212 (TAAB, Aldermaston, UK) as previously reported (Mastrodonato et al, 2009). Ultrathin sections were mounted on formwar-coated nickel mesh grids and stained with uranyl acetate and lead citrate (Reynolds, 1963).…”
Section: Electron Microscopymentioning
confidence: 99%
“…ransmission electron microscopy. The eggs were fixed in 4% glutaraldehyde and processed for embedding in Epoxy Resin-Araldite (M) CY212 (TAAB, Aldermaston, UK) as previously reported [46]. Semi-thin sections 2 μm thick were stained with Toluidine blue-PAS (PAS-TB).…”
Section: T T T T Transmission Electron Microscopymentioning
confidence: 99%